Osteogenic and Chondrogenic Potential of Periosteum-Derived Mesenchymal Stromal Cells: Do They Hold the Key to the Future? - Madhan Jeyaraman; Sathish Muthu; Prakash Gangadaran; Rajni Ranjan; Naveen Jeyaraman; Gollahalli Shivashankar Prajwal; Prabhu Chandra Mishra; Ramya Lakshmi Rajendran; Byeong-Cheol Ahn (MDPI AG, 2021)
The periosteum, with its outer fibrous and inner cambium layer, lies in a dynamic environment with a niche of pluripotent stem cells for their reparative needs. The inner cambium layer is rich in mesenchymal progenitors, osteogenic progenitors, osteoblasts, and fibroblasts in a scant collagen matrix environment. Their role in union and remodeling of fracture is well known. However, the periosteum as a source of mesenchymal stem cells has not been explored in detail. Moreover, with the continuous expansion of techniques, newer insights have been acquired into the roles and regulation of these periosteal cells. From a therapeutic standpoint, the periosteum as a source of tissue engineering has gained much attraction. Apart from its role in bone repair, analysis of the bone-forming potential of periosteum-derived stem cells is lacking. Hence, this article elucidates the role of the periosteum as a potential source of mesenchymal stem cells along with their capacity for osteogenic and chondrogenic differentiation for therapeutic application in the future.